Mu’tazilah and the Digital Era: Reinterpreting Islamic Tafsir in the Era of Artificial Intelligence (AI) - Hamdi, Thon Thowi; Suqiyah Musafa’ah; Rizkiyah Hasanah (Jurnal Semiotika-Q, 2025)
The development of technology in the digital era, especially artificial intelligence (AI), demands an update in the approach to Islamic interpretation. This study aims to analyze how the principles of Mu'tazilah rationality can be integrated with the development of AI to interpret Islam in the modern era. The research approach uses a qualitative method with a case study design. The study subjects included Mudzir Ma'had Aly Probolinggo, Head of the Study Program, Musyrif, the IT Team, and Mahasantri. Data collection techniques were done through in-depth interviews, literature studies, and digital document analysis. Data analysis includes  data  reduction,  data  presentation, and  conclusion.  The  study   results indicate that using AI in Islamic interpretation can expand the understanding of classical texts with a more rational, contextual, and inclusive approach. The Mu'tazilah perspective provides a philosophical foundation for aligning artificial intelligence with the principles of Justice, reason, and humanity. This has proven effective in creating a new dialogue space that supports the renewal of Islamic thought in the digital era. This study contributes significantly to efforts to understand Islam through the lens of modern technology while adhering to the principles of faith and rationality. The development of technology in the digital era, especially artificial intelligence (AI), demands an update in the approach to Islamic interpretation. This study aims to analyze how the principles of Mu'tazilah rationality can be integrated with the development of AI to interpret Islam in the modern era. The research approach uses a qualitative method with a case study design. The study subjects included Mudzir Ma'had Aly Probolinggo, Head of the Study Program, Musyrif, the IT Team, and Mahasantri. Data collection techniques were done through in-depth interviews, literature studies, and digital document analysis. Data analysis includes  data  reduction,  data  presentation, and  conclusion.  The  study   results indicate that using AI in Islamic interpretation can expand the understanding of classical texts with a more rational, contextual, and inclusive approach. The Mu'tazilah perspective provides a philosophical foundation for aligning artificial intelligence with the principles of Justice, reason, and humanity. This has proven effective in creating a new dialogue space that supports the renewal of Islamic thought in the digital era. This study contributes significantly to efforts to understand Islam through the lens of modern technology while adhering to the principles of faith and rationality.